Does Gender Inclusivity Matter for Economic Growth in South Africa? An ARDL approach - Khutso Baltimore Makua; Neo Malungane; Khayakazi Mswephu; Ronewa Candy Sadiki (Journal of Economics, Business, and Accountancy Ventura, 2022)
With inequality at the forefront of economic development, this paper examined the impact of gender inequality on economic growth in South Africa. Different gender dimensions were considered, including female education, female labor force participation, fertility, and the representation of women in the political arena (democracy). The research applied a quantitative approach (Autoregressive Distributive lag) (ARDL) with secondary data on the proportion of all variables spanning from 1989 to 2019. The results revealed that high fertility negatively affects economic growth. Moreover, the effects are positive when women have greater access to secondary education and the labor market. However, an unorthodox finding from the study reveals that the effects are negative when women have access to political seats in parliament. The paper recommends that policymakers should focus on guaranteeing obligatory secondary education for females in the country. Additionally, policymakers should introduce measures that favor appointing and absorbing women in qualified jobs.